Water sharing, reciprocity, and need: A comparative study of interhousehold water transfers in sub‐Saharan Africa. Issue 2 (31st January 2019) - Brewis, Alexandra; Rosinger, Asher; Wutich, Amber; Adams, Ellis; Cronk, Lee; Pearson, Amber; Workman, Cassandra; Young, Sera; ,
Abstract : Water sharing between households could crucially mitigate short‐term household water shortages, yet it is a vastly understudied phenomenon. Here we use comparative survey data from eight sites in seven sub‐Saharan African countries (Democratic Republic of the Congo, Ethiopia, Ghana, Kenya, Malawi, Nigeria, and Uganda) to answer three questions: With whom do households share water? What is expected in return? And what roles do need and affordability play in shaping those transfers? We find that water is shared predominantly between neighbors, that transfers are more frequent when water is less available and less affordable, and that most sharing occurs with no expectation of direct payback. These findings identify water sharing, as a form of generalized reciprocity, to be a basic and consistent household coping strategy against shortages and unaffordability of water in sub‐Saharan Africa.